Baseline Circulating FGF21 Concentrations and Increase after Fenofibrate Treatment Predict More Rapid Glycemic Progression in Type 2 Diabetes: Results from the FIELD Study. (6th January 2020) - Ong, Kwok-Leung; O'Connell, Rachel; Januszewski, Andrzej S; Jenkins, Alicia J; Xu, Aimin; Sullivan, David R; Barter, Philip J; Scott, Russell S; Taskinen, Marja-Riitta; Waldman, Boris; Colman, Peter G; Best, James D; et al.
Abstract: BACKGROUND: It is not known whether circulating fibroblast growth factor 21 (FGF21) concentrations are associated with glycemic progression in patients with established type 2 diabetes. This study reports this relationship in type 2 diabetes patients participating in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) trial. METHODS: Plasma FGF21 was quantified in 9697 study participants. Among patients with lifestyle-only glucose control measures at baseline, glycemic progression was defined as the initiation of oral hypoglycemic agents or insulin therapy. We assessed the relationship of FGF21 concentrations with glycohemoglobin (Hb A1c ), the homeostasis model assessment of β-cell function (HOMA-B) and insulin resistance (HOMA-IR), and glycemic progression. RESULTS: Among 2584 patients with lifestyle-only glycemic therapy at baseline, plasma FGF21 concentrations were positively associated with HOMA-IR (5.1% increase per 100% increase in FGF21 concentrations). Patients with higher baseline plasma FGF21 concentrations had higher risk of glycemic progression over a 5-year period ( P = 0.02), but the association was not significant after further adjusting for alanine aminotransferase (ALT) enzyme activity. During the fenofibrate active run-in phase, higher tertiles of fenofibrate-induced increase in FGF21 concentrations were associated with higher risk of glycemic progression (adjusted hazards ratio = 1.09 and 1.18 for tertiles 2 and 3, respectively, P for trend = 0.01), even after adjusting for ALT enzyme activity. This association was statistically significant in the fenofibrate group only ( P = 0.01). CONCLUSIONS: Higher baseline and fenofibrate-induced increase in FGF21 concentrations predict more rapid glycemic progression in type 2 diabetes patients. This association may be partly explained by hepatic function.